The political mind, or, 'How to think differently' - Laird, Kieran (Edinburgh University Press, 2008)
What does it mean to 'think differently'? The ability to create thoughts is what lies at the base of philosophy and political theory and practice. One cannot hope to change the world, or even adequately critique it, without the possibility of the new in mental life. The Political Mind explores the possibility of thinking differently through connecting neuropsychological material on consciousness, nonconsciousness and affect to political theory. It spans diverse disciplines: from hard-edged neuropsychology to sociology, economics, political theory and Eastern and Western philosophy. Its originality lies in its ability to draw meaningful connections between such disparate literatures, weaving a coherent whole. It then applies the concepts created to the currently popular topics of consumerism and the anti-capitalist and anti-globalisation movements. Key Features Explores the manufacture of the self in consumer society*Suitable for readers interested in philosophy of mind, poststructuralist political theory, and connections between psychology, sociology and politics*Adds to a small but growing literature regarding the interconnection between neuropsychology and politics